On the merits and shortcomings of semantic primes and natural semantic metalanguage in cross-cultural translation - Trobevšek Drobnak, Frančiška (ELOPE (Ljubljana), 2009)
The purpose of this paper is to review some basic postulates of the theory of semantic primitives (semantic primes) and to evaluate the applicability of the natural semantic metalanguage in cross-cultural translation. The theory of semantic primes, formulated by Anna Wierzbicka and her colleagues, posits a universal set of cognitive primitives, lexicalized in all natural languages, which, combined into canonical sentences of basic syntactic patterns, constitute a natural semantic metalanguage (NSM). NSM is put forward as an alternative to traditional lexicographic definitions of words, to componential and prototypical semantic analysis, and, as tertium comparationis, presented as a more effective tool in translating culture-specific words and ethnosyntactic features.
Keywords: canonical sentence; cognitive syntax; cross-cultural translation; kanonični stavek; kognitivna skladnja; medkulturni prevod; naravni pomenski metajezik; natural semantic metalanguage; prapomen; prevajanje; semantic prime; translation